BIOFILM DARI PATI BIJI NANGKA DENGAN ADDITIF KARAGINAN - Bunga Chrismaya; Fransisca Selvy; Diah S. Retnowati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Jackfruit (Artocarpus heterophyllus) have cotyledons layer which is rich in starch and can be use as biofilm forming material. Biofilm is a film made from renewable material such as starch. Biofilm made from native starch have poor mechanical properties such as tensile strength and elongation at break. To overcome it, starch is blending with other material that can improve tensile strength and elongation at break. Kappa carageenan had firm gel structures and could be used to improve tensile strength and elongation at break of starch biofilm. Biofilm was made by casting polymer solution prepared by heating the mixture solution consisting of starch and carrageenan with a certain weight ratio dissolved in water-glycerol solution with a certain weight ratio with heating rate 2,2oC until the temperature reached 95oC. The biofilms that had been casted then dried in oven at 50oC for 20 hours and aged for 7 days at room temperature and relative humidity prior before tensile strength and elongation at break test. The results showed that kappa-carrageenan jackfruit seed starch biofilm has higher tensile strength and elongation at break than biofilm made from native starch. When the weight ratio of glycerol rose, resulted in decreased tensile strength and increase in elongation at break biofilms. The best tensile strength was 0.407 MPa for 50%w/w kappa carrageenan and the weight 10%w/w glycerol. In addition, the best elongation at break was 18,488% at 50% w/w kappa carrageenan and 20% w/w glycerol.